Professional Jakarta Struts - Goodwill James; Hightower Richard (Indiana : Wiley, 2003)
Jakarta Struts-a Java Open Source product-is the most popular framework for building enterprise-level Web applications and has become a dominant force in Java Web application development
* This is the first book on the market to provide Java developers with the concepts and code they need to build sophisticated, enterprise-level Web applications using the final production release of Struts 1.1
* Demonstrates best programming practices and power developer techniques
* Features a strong focus on Struts and its MVC architecture
Keywords: Web Applications; Java serviet--Java sever